CALCULATION OF CREDITED INTEREST RATE WITH INVESTMENT YEAR METHOD AND PORTFOLIO METHOD - Aryento, Jevilia; Kusnadi, Felivia; Lesmono, Dharma (PATTIMURA UNIVERSITY, 2022)
The rate of return on investment for unit-linked insurance products in Indonesia is still volatile and depends on the investment instruments performance. However, the net return on investment that is given to policyholders is projected at the beginning of the year and is used as a benchmark for choosing the right investment instrument, referred to as the credited interest rate. Interest rates movements affect the yield of the credited interest rate. Therefore, the credited interest rate calculation requires appropriate methods to reduce the risk of loss, which are the Investment Year Method and the Portfolio Method. Research shows that the Investment Year Method is more appropriate in unstable interest rate condition, whereas the Portfolio Method is better utilized in a stabilized environment. In addition, this research also shows the strategy to manage investment instruments with asset rollover to suit the fluctuating credited interest rate.